2015
DOI: 10.1016/j.reprotox.2015.07.077
|View full text |Cite
|
Sign up to set email alerts
|

Soy but not bisphenol A (BPA) or the phytoestrogen genistin alters developmental weight gain and food intake in pregnant rats and their offspring

Abstract: Endocrine disrupting compounds (EDCs) are hypothesized to promote obesity and early puberty but their interactive effects with hormonally active diets are poorly understood. Here we assessed individual and combinatorial effects of soy diet or the isoflavone genistein (GEN; administered as the aglycone genistin GIN) with bisphenol A (BPA) on body weight, ingestive behavior and female puberal onset in Wistar rats. Soy-fed dams gained less weight during pregnancy and, although they consumed more than dams on a so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 74 publications
1
29
0
1
Order By: Relevance
“…Alternatively, lower levels of TBBA found in the urine of lactating dams could be a result of simple dilution, as both gestating and lactating dams were allowed water ad libitum. In fact, there is evidence that lactating Sprague Dawley rats drink, on average, more water than their gestating counterparts (Cao et al, 2015;Slone et al, 2012). This is also supported by the high variability in urinary TBBA levels, indicating differential water intake (Fig.…”
Section: Brominated Metabolitesmentioning
confidence: 80%
“…Alternatively, lower levels of TBBA found in the urine of lactating dams could be a result of simple dilution, as both gestating and lactating dams were allowed water ad libitum. In fact, there is evidence that lactating Sprague Dawley rats drink, on average, more water than their gestating counterparts (Cao et al, 2015;Slone et al, 2012). This is also supported by the high variability in urinary TBBA levels, indicating differential water intake (Fig.…”
Section: Brominated Metabolitesmentioning
confidence: 80%
“…Complete study design details are described in a prior study in which we used the same animals (Cao et al, 2015). Briefly, 54 pairs of Wistar rats were obtained and their offspring tested for these experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The soy diet was a custom diet (Harlan Laboratories, Madison, WI) with maximum similarity to Teklad 2020 with isoflavone levels ~400 mg/kg diet. Effects on growth, body weight, age at puberty and other developmental parameters for these animals are detailed in a prior publication (Cao et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Andreoli et al (2015) also reported that feeding adult male Wistar rats a low phytoestrogen diet induced obesity and impaired glucose metabolism. Conversely, exposure of Wistar rats to a soy meal-containing diet during development has been reported to result in increased adult body weight in males, but not females (Cao et al, 2015), while developmental exposure of Sprague-Dawley rats to genistein was reported to result in obese adult females, but not males (Strakovsky et al, 2014). Lifetime exposure of Sprague-Dawley rats to 500 ppm, but not 5 or 100 ppm, genistein reduced body weight gain in the F 1 and F 2 generation females and in the F 1 generation males (National Toxicology Program, 2008a).…”
Section: Introductionmentioning
confidence: 99%